Analisis Kompetensi Kewirausahaan dalam Mewujudkan Keunggulan Kompetitif di UMKM Kedai Mie Ala Korea Kecamatan Lemahabang Wadas - Anggraeni, Fadilah Anggun; Marliani, Sari; Yuliawati, July (Journal of Management and Bussines (JOMB), 2024)
This study aims to analyze how entrepreneurial competence can realize competitive advantage in Korean Noodle Shop MSMEs located in Wadas Lemahabang, which offers various Korean specialties. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study indicate that Korean Noodle Shops have entrepreneurial competence that includes the ability to create new flavors, consistency in posting products on social media, the ability to prepare financial reports, and the presence of business partners. Competitive advantages include special spice blends, competitive pricing, and the ability to survive and compete for six years. The obstacles faced include a location far from the city center, lack of use of digital marketing, some raw materials purchased online, and long-lasting service. The proposed solutions to overcome these obstacles include opening a branch in the city center, registering sales through digital marketing, stocking raw materials for the next few days, adding local business partners, and training for chefs to improve service speed. This study provides important insights for the development of entrepreneurial strategies to increase the competitive advantage of MSMEs in the culinary sector. Keywords: Korean Noodle Shop, Entrepreneurial Competence, Competitive Advantage